Optimization of temperature and time in carrageenan extraction of seaweed (Kappaphycus alvarezii) using ultrasonic wave extraction methods. (November 2019) - Mahyati,; Azis, Abdul
Abstract: Carrageenan is a hydrocolloid compound from Rhodophyceae extraction of K. alvarezii using alkali solvents. Conventional extraction methods that have been using certain solvents in large volumes require a long time and low yields resulting in high production costs and large amounts of waste which pollute the environment. These adverse effects can be minimized by extraction with the help of ultrasonic waves which will provide an intensive stirring effect to damage the cell walls of seaweed so that the process of mass transfer will be faster. The extraction temperature greatly influences the quantity and quality of carrageenan which is often carried out in conventional extraction. In carrageenan extraction activities from K. alvarezii with the help of ultrasonic waves, the effects of temperature and time on these two parameters will also be studied. This activity was conducted to determine the time and temperature of carrageenan extraction from K. alvarezii seaweed using an ultrasonic frequency of 40 kHz with temperature variations of 30, 40, 50, 60, and 70 °C, and time variations of 20, 25, 30, 35 and 40 minutes. The results of extraction of K.alvarezii seaweed with a time variation of 40 minutes and temperature variation is 70 °C, with the optimum value of temperature and extraction time is 70 °C for 30 minutes which produces carrageenan as much as 44.46%. The carrageenan quality test produced water content ranging from 6.27-14.18%, ash content 12.33-13.69%, viscosity of 10.4-27.9 cP and gel strength ranged from 926.26 to 4945.99 dyne / cm 2 .